The relation between organizational commitment and managerial effectiveness of instructors at schools of physical education and sports - Erkan Faruk Sırın; Eyup Dalkıran (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to verify whether there is a relation between managerial effectiveness and organizational commitments of the instructors who work at SPES (School of Physical Education and Sports) that are considered as organizations. The study was carried out with a group of 232 instructors voluntarily participating in the research from 29 SPES. The research data were collected through "Personal Information Form", "Organizational Commitment Scale" and "Managerial Effectiveness Scale". In the study, data were analyzed with descriptive statistical procedures such as frequency, percentage, arithmetic mean, standard deviation and correlation. At the end of the research, it was observed that the instructors generally have a strong commitment to their organizations and that they perceived their administrators’ managerial effectiveness as “partially agree”, the perception of the sense of managerial effectiveness of their administrators is medium.  It was identified that there is a positive correlation between emotional commitment extent of organizational commitment scale and all sub-extents of managerial effectiveness; low positive correlation between the continuation dimensions of the organization; and there is a medium level of the positive correlation between the normative extent of organizational commitment and all sub-extents of managerial effectiveness.